Characterization of temporal trends of systolic and diastolic indexes over time in breast cancer patients treated with trastuzumab. (4th February 2022) - Cardoso, A; Tinoco, M; Von Hafe, P; Dias, G; Pereira, T; Oliveira, L; Fernandes, M; Azevedo, O; Lourenco, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Trastuzumab therapy increases survival in patients (pts) with HER2 positive breast cancer, however, it is associated with a risk of cardiotoxicity (CT). Our aim was to: 1) assess the temporal evolution of systolic and diastolic left and right ventricular indexes during and after T therapy and 2) study the incidence of CT in this group. Methods: Retrospective study of breast cancer pts treated with T in a single center, during 2017 and 2018, who underwent a comprehensive echocardiographic examination before, quarterly, and after conclusion of T therapy. Pts with a baseline left ventricular ejection fraction (EF) <50% were excluded. CT was defined as a reduction of EF >10% to a value <50% or as a relative reduction of global longitudinal strain (GLS) of more than 15%. Results: We included 50 women with mean age of 56 ± 10 years and mean body mass index (BMI) of 27 ± 5 kg/m2. Thirty-six (72%) patients underwent anthracycline chemotherapy prior to T and 44 (88%) had performed radiotherapy. During treatment with T there was an increase of indexed left ventricle end-diastolic volume (38.6 ± 7.8 to 46.5 ± 10.3 ml/m2, p<.001) and a reduction of LVEF (65.1 ± 5.4 to 59.3 ± 6.2%, p < 0.001), GLS (-21.2 ± 2.7 to -17.9 ± 2.8%, p<.001) and right ventricle S' (14.4 ± 13.1 to 12.2 ± 1.6 cm/s, p<.001) compared to baseline. There was no change in diastolic function parameters. CT occurred in 23 (46%) pts, the majority based on GLS criteria (18; 78%). Heart failure symptoms were reported in 4 (8%) of these pts (1 in the GLS group and 3 in the EF group) and 3 (6%) pts had to permanently suspend therapy with T due to CT. Patients with CT had a lower BMI (25 ± 4 vs 29 ± 4 kg/m2), but were otherwise similar to pts without CT. No association was found between pre-treatment with anthracyclines or radiotherapy with the risk of CT. An echocardiographic revaluation at 2 years from treatment with T revealed a tendency for LVEF improvement (58.7 ± 7.1 to 61.2 ± 6.3%, p=.059) and a significative recovery of GLS (-17.4 ± 3.5 to -19.1 ± 3.3%, p=.026). No significative variations were found on right ventricular systolic function indexes or on diastolic parameters. During a follow-up of 43 (IQR 32–47) months, 7 (14%) pts had tumor relapse and 1 (2%) died. CT was not associated with the composite endpoint of tumor relapse or death (p = 0.585). Conclusion: T therapy is associated with a significative reduction on left and right ventricle systolic indexes during treatment. Although left ventricle systolic function tends to normalize over time, this does not happen with the right ventricle. CT induced by T had clinical impact leading to overt heart failure in 8% of pts and treatment discontinuation in 6% of pts. A lower BMI was associated with CT, which may be taken into account when defining the treatment strategy.